Advocating Legal Certainty in Status Transition of Individual Companies Exceeding MSEs Criteria to Limited Liability - Wiriatma, Dodo Wiradana; Admiral, Admiral; Hamzah, Rosyidi; Febrianto, Surizki; Syafrinaldi, Syafrinaldi; Hyeonsoo, Kim (Indonesian Journal of Advocacy and Legal Services, 2025)
The enactment of Law Number 6 of 2023, concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 on Job Creation, introduced the Individual Company as a legal entity designed to empower Micro and Small Enterprises (MSEs). This provision enables the establishment of a company by a single individual, a departure from the traditional requirement of at least two shareholders. The Job Creation Law, supported by Government Regulation Number 8 of 2021, outlines that an Individual Company is created through a Statement of Establishment, without the need for a Notary Deed, in line with the provisions for MSEs as stipulated in Government Regulation Number 7 of 2021. However, this legal framework creates challenges when an Individual Company exceeds the MSE criteria or gains more than one shareholder. In such cases, the company must transition into a Limited Liability Company (LLC), a process that requires the drafting of a notary deed and registration through the Ministry of Law and Human Rights’ online AHU system. This research focuses on advocating for legal certainty in the status transition of Individual Companies to Limited Liability Companies, which currently involves the dissolution of the original entity before the new LLC can be formed. The lack of a clear, comprehensive legal mechanism for this transition causes significant legal uncertainty. This paper examines the gaps in the existing legal framework and proposes solutions to streamline the conversion process, eliminating the need for dissolution. By advocating for legal certainty in the status transition, this research contributes to the broader discourse on improving the General Legal Administration system, ensuring that the legal status of businesses aligns with their evolving needs, and facilitating smoother business expansion and growth.